Capacity development in household surveys experience from the centre for development data training initiative - Kanyanda, Shelton; Kouadio, Hugues; McGee, Kevin; Zezza, Alberto (Statistical journal of the IAOS, 2021)
Household surveys remain the major source of official statistics for monitoring development policies particularly in developing countries. In the context of rapid developments in data needs, extensive methodological work, data processing and use at national and international levels and a remaining capacity gap despite efforts for statistical capacity building in last decade, it is critical for training centers to keep up to speed with international best practices. This paper show that the approach of the Centre for Development Data Training initiative (C4D2 Training Initiative) is highly effective and stand to have a long-term impact on household survey capacity in Africa region. It is made of several components all of which aim to bolster capacity development in the region. It harmonizes and improves the quality and sustainability of training on household surveys through increased local capacity and greater dissemination of best practices, creates a network among participants and trainers to facilitate knowledge exchange on best practices as well as survey harmonization across countries. Taking advantage of benefits, the initiative should endeavor other regions subject to their interest and embrace the use of virtual and web-based training.